Koli woman decorating with rangoli - Mumbai Archive Project Team (Jio Institute, 2024)
On the first day, families come together to clean and decorate their homes and the community spaces. Homes are decorated with flowers, rangoli (intricate patterns made with coloured powders), and oil lamps.